Stress Kerja dan Lingkungan Kerja pada Kinerja Karyawan di BAZNAS - Marlina, Ana; Ali, Rustan; Saripah, Saripah; Rifani, Riza Amalia (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study aims to determine the effect of work stress and work environment partially on employee performance at the National Amil Zakat Agency Office in Enrekang Regency. To find out that work stress and work environment have a simultaneous effect on employee performance at the National Amil Zakat Agency Office in Enrekang Regency. The analytical method used is descriptive analysis using data sourced from the results of the questionnaires that have been answered by the respondents. The tests used include Validity Test, Reliability Test, Descriptive Analysis, Multiple Linear Regression Analysis and Test (partial), F Test (simultaneous), R2 Test (Coefficient of Determination). These results indicate that work stress does not partially affect employee performance at the Enrekang Regency National Amil Zakat Agency, the work environment has a positive and significant effect on employee performance at the Enrekang District National Amil Zakat Agency office, work stress and work environment simultaneously influence employee performance at the Enrekang District National Amil Zakat Agency office.